(untitled) (World Science, 2022)
The problem of lactose metabolism remains relevant from the standpoint of various areas of medical research. Clinicians, anthropologists, physiologists and geneticists are engaged in the study of lactose digestion devices and various types of disorders associated with it, including lactose intolerance. Determination of such mechanisms allows us to understand not only the nutritional causes of the development of functional intestinal symptoms, but also the evolution of man and nutrition, culture and lifestyle. Symptoms of lactose intolerance are abdominal pain, flatulence, nausea, bloating, and diarrhea after drinking milk or dairy products. These symptoms may be caused by malabsorption of lactose, which is the result of low levels of lactase in the small intestine. Symptoms also occur after consumption of lactose or lactose products, with no apparent effect on the human microbiota and overall health. Therefore, of particular concern are the strict dairy-free diets commonly prescribed for patients with such complaints. This article discusses modern recommendations for the diagnosis and treatment of lactose malabsorption and lactose intolerance, which largely comply with European recommendations.